Experimental and computational insight in molecular interactions of ternary mixtures of ethyleneglycoldiacetate+ 4-methylacetophenone + dibutylamine at T = (298.15 to 318.15) K - Masumeh Farahani Farvazi; Hossein Iloukhani; Khatereh Khanlarzadeh (Scientific Reports)
Abstract The thermodynamic properties of the ternary system consisting of ethyleneglycoldiacetate (EGDA), 4-methylacetophenone (4-MeAP), and dibutylamine (DBA), along with their binary components, were investigated at temperatures ranging from 298.15 to 318.15 K and at ambient pressure. Measurements included density (ρ), speed of sound (u), and refractive index ( $$\:{n}_{D}$$ ). The properties calculated from these measurements included excess molar volumes $$\:{\:V}_{m}^{E}$$ , deviations in isentropic compressibility Δ $$\:K_{\text{s}}$$ , and refractive index changes $$\:\varDelta\:{n}_{D}$$ . These excess or deviation properties were analyzed using the Redlich–Kister and Cibulka equations, respectively. Additionally, the measured densities were utilized to evaluate the validity of the Perturbed-Chain Statistical Associating Fluid Theory (PC-SAFT) equation of state, which showed good agreement with experimental results. The quantities studied provide insights into the nature and strength of intermolecular interactions between similar and dissimilar molecules.